A novel cold-adapted type I pullulanase of Paenibacillus polymyxa Nws-pp2: in vivo functional expression and biochemical characterization of glucans hydrolyzates analysis. Issue 1 (December 2015) - Wei, Wei; Ma, Jing; Chen, Si-Qi; Cai, Xiang-Hai; Wei, Dong-Zhi
Abstract Background Pullulanase is an important debranching enzyme and has been widely utilized to hydrolyse the α-1, 6 glucosidic linkages in starch/sugar industry. Selecting new bacterial strains or improving bacterial strains is a prerequisite and effective solution in industrial applications. Although many pullulanase genes have been cloned and sequenced, there is no report ofP. polymyxa type I pullulanase gene or the recombinant strain. Meanwhile most of the type I pullulanase investigated exhibit thermophilic or mesophilic properties. There are just few reports of cold-adapted pullulanases, which have optimum activity at moderate temperature and exhibit rather high catalytic activity at cold. Previously, six strains showing distinct pullulan degradation ability were isolated using enrichment procedures. As containing novel bacterium resource and significant pullulanase activity, strain Nws-pp2 was selected for in-depth study. Methods In this study, a type I pullulanase gene (pulN) was obtained from the strain P. polymyxa Nws-pp2 by degenerate primers. Through optimization of induced conditions, the recombinant PulN achieved functional soluble expression by low temperature induction. The enzyme characterizations including the enzyme activity/stability, optimum temperature, optimum pH and substrate specificity were also described through protein purification. Results The pullulanase gene (namedpul N), encoding a novel cold-adapted type I pullulanase (named PulN ), was obtained from isolated strainPaenibacillus polymyxa Nws-pp2. The gene had an open reading frame of 2532-bp and was functionally expressed inEscherichia coli through optimization of induced conditions. The level of functional PulN -like protein reached the maximum after induction for 16 h at 20 °C and reached about 0.34 mg/ml (about 20 % of total protein) with an activity of 6.49 U/ml. The purified recombinant enzyme with an apparent molecular mass of about 96 kDa was able to attack specifically the α-1, 6 linkages in pullulan to generate maltotriose as the major product. The purified PulN showed optimal activity at pH 6.0 and 35 °C, and retained more than 40 % of the maximum activity at 10 °C (showing cold-adapted). The pullulanase activity was significantly enhanced by Co2+ and Mn2+, meanwhile Cu2+ and SDS inhibited pullulanase activity completely. TheKm andVmax values of purified PulN were 15.25 mg/ml and 20.1 U/mg, respectively. The PulN hydrolyzed pullulan, amylopectin, starch, and glycogen, but not amylose. Substrate specificity and products analysis proved that the purified pullulanase fromPaenibacillus polymyxa Nws-pp2 belong to a type I pullulanase. Conclusions This report of the novel type I pullulanase inPaenibacillus polymyxa would contribute to pullulanase research fromPaenibacillus spp. significantly. Also, the cold-adapted pullulanase produced in recombinant strain shows the potential application.